2006
DOI: 10.1095/biolreprod.105.043695
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the ADRB3 Adrenergic Receptor Induces Relaxation of Human Placental Arteries: Influence of Preeclampsia1

Abstract: Preeclampsia, which complicates 3-8% of pregnancies, is one of the leading causes of neonatal morbidity and mortality. Its pathophysiology remains unclear. The aim of the present study was to investigate the presence and the role of beta2- and beta2-adrenergic receptors (ADRB2 and ADRB3, respectively) in human placental arteries and to assess the influence of preeclampsia on ADRB responsiveness. SR 59119A, salbutamol, and isoproterenol (ADRB3, ADRB2, and nonselective ADRB agonists, respectively) induced a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
2
8
1
Order By: Relevance
“…These antibodies have been previously used by other authors to detect the expression of ␤1-and ␤2-ARs (Naren et al, 2003;Liang and Fishman, 2004;Rouget et al, 2006). In the present study, we performed both positive and negative control experi- ments and demonstrated the specificity of the ␤1-and ␤2-AR antibodies.…”
Section: Discussionsupporting
confidence: 60%
“…These antibodies have been previously used by other authors to detect the expression of ␤1-and ␤2-ARs (Naren et al, 2003;Liang and Fishman, 2004;Rouget et al, 2006). In the present study, we performed both positive and negative control experi- ments and demonstrated the specificity of the ␤1-and ␤2-AR antibodies.…”
Section: Discussionsupporting
confidence: 60%
“…Our findings confirm and extend those of Rouget and coworkers, who recently showed that the presence of preeclampsia did not influence the mRNA expression levels of β 2 -AR and β 3 -AR in placental vessels isolated from the chorionic plate (20). However, a difference was observed between the study by Rouget and colleagues (20) and the present study in relation to β 3 -AR protein expression.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, recent evidences suggest that Adrb1 appear to be mainly responsible for vasorelaxation in mouse (Chruscinski et al, 2001) and rat mesenteric resistance arteries (MRA) (Briones et al, 2005), and mediate smooth muscle hyperpolarization in rat MRA (Garland et al, 2011). In addition, the participation of Adrb3 in the vasorelaxant response has also been documented in some blood vessels, such as the rat carotid artery (Oriowo, 1994), rat (Sooch and Marshall, 1997) and canine (Tagaya et al, 1999) pulmonary artery, the human internal mammary (Rozec et al, 2005) and placental (Rouget et al, 2006) arteries, and also in coronary microarteries (Dessy et al, 2004). Nevertheless, there have been conflicting reports on Adrb3 involvement in vasodilator responses in rat aorta.…”
Section: Introductionmentioning
confidence: 99%